In situ electrochemical observation of anisotropic lattice contraction of La0.6Sr0.4FeO3−δ electrodes during pulsed laser deposition. Issue 1 (7th December 2022) - Riedl, Christoph; Siebenhofer, Matthäus; Ražnjević, Sergej; Bumberger, Andreas Ewald; Zhang, Zaoli; Limbeck, Andreas; Opitz, Alexander Karl; Kubicek, Markus; Fleig, Jürgen
Abstract : The electrochemical effects of anisotropic lattice deformation during La0.6 Sr0.4 FeO3− δ growth by pulsed laser deposition are investigated by in situ impedance spectroscopy. Abstract : La0.6 Sr0.4 FeO3− δ (LSF) electrodes were grown on different electrolyte substrates by pulsed laser deposition (PLD) and their oxygen exchange reaction (OER) resistance was tracked in real-time by in situ PLD impedance spectroscopy (i-PLD) inside the PLD chamber. This enables measurements on pristine surfaces free from any contaminations and the direct observation of thickness dependent properties. As substrates, yttria-stabilized zirconia single crystals (YSZ) were used for polycrystalline LSF growth and La0.95 Sr0.05 Ga0.95 Mg0.05 O3− δ (LSGM) single crystals or YSZ single crystals with a 5 nm buffer-layer of Gd0.2 Ce0.8 O2− δ for epitaxial LSF film growth. While polycrystalline LSF electrodes show a constant OER resistance in a broad thickness range, epitaxially grown LSF electrodes exhibit a continuous and strong increase of the OER resistance with film thickness until ≈60 nm. In addition, the activation energy of the OER resistance increases by 0.23 eV compared to polycrystalline LSF. High resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) measurements reveal an increasing contraction of the out-of-plane lattice parameter in the epitaxial LSF electrodes over electrode thickness. Defect thermodynamic simulations suggest that the decrease of the LSF unit cell volume is accompanied by a lowering of the oxygen vacancy concentration, explaining both the resistive increase and the increased activation energy.